Impact of User Experience Using Generative AI in Software Development Life Cycle - Dhandapani, Sowmya (Global journal of Business and Integral Security, 2025)
In the recent days, Generative Artificial intelligence is revolutionizing the way creativity is perceived. It helps in expanding the horizons of generating new content through self-learning algorithms. While the leverage of Generative AI is already being widely explored for creation of documents, pictures, videos and audio content, this research is to evaluate its impact in the software development. The intended research was to understand the current user experience models in the software development, learn the impact of Gen AI on the user experience developers and designers. Based on the exploration, the research provides a model through which Gen AI can be smoothly integrated with User Experience Development. This helped in bringing together the three areas of Generative AI, User Experience and Software Development together to provide a positive impact for the business as well as the technology team. The research involved understanding the current industry practices, and readiness for new technology through a survey. Based on the responses of the survey, a new model was proposed on how the integration of Gen AI and User Experience can be achieved in the software development lifecycle. This model was validated with case studies to confirm if aligns with the expected output.